Resolution of Business Disputes in the Aviation Industry: The Role of Law and Arbitration - Suryawan, Ryan Firdiansyah; Sungkono; Endah Yuniarti (Dinasti Research, 2023)
The purpose of this study is to explore the legal framework governing dispute resolution, examine the practice of using arbitration, identify the challenges faced, and provide recommendations to improve the effectiveness of business dispute resolution in the aviation industry. Conduct a review of the relevant literature to understand the legal framework governing business dispute resolution in the aviation industry, as well as practices and trends in the use of arbitration. Analyze data obtained from literature studies, case analysis, and, trends, and findings relevant in the context of business dispute resolution in the aviation industry. The role of arbitration law and implementation in the resolution of business disputes in the aviation industry is of significant importance. Law governs operational aspects and handles conflicts, while arbitration offers efficient and transparent solutions. The focus on investment risk prevention, regulatory updates, and negotiation methods demonstrate efforts to improve a conducive business environment. Consumer protection and law enforcement are necessary to ensure fairness for all parties. Thus, efforts to increase the role of arbitration law and implementation can bring great benefits in the aviation industry.